(untitled) (Research, Society and Development, 2023)
An access it is a road equipment defined as a intersection of a highway with an connection path to marginal properties. The accesses exert great influence over the conditions of trafficability in the highways, may cause dangerous situations or discomfort to the users when miss designed. To avoid unpleasant situations like this, the accesses must be designed according with the prescriptions established in the DNIT’s manual (Departamento Nacional de Infraestrutura de Transportes). In observance of the scope of such manuals, this paper shows an analysis of the geometrical characteristics of an access built on the highway BR-415, Km 13, in the city of Ilhéus-BA, which serves as a Robson de Andrade Braga Integrated Unity, which belongs to FIEB (Federação das Indústrias do Estado da Bahia) system. After being verified the geometric insufficiency in the existent access, a new geometrical reconfiguration has been elaborated which lays on the recommendation stated in DNIT manuals.